What is chronic fatigue syndrome? Heterogeneity within an international multicentre study. - Wilson, A; Hickie, I; Hadzi-Pavlovic, D; Wakefield, D; Parker, G; Straus, SE; Dale, J; McCluskey, D; Hinds, G; Brickman, A; Goldenberg, D; Demitrack, M; et al. (2001)
OBJECTIVE: We sought to compare the characteristics of patients presenting with chronic fatigue (CF) and related syndromes in eight international centres and to subclassify these subjects based on symptom profiles. The validity of the subclasses was then tested against clinical data. METHOD: Subjects with a clinical diagnosis of CF completed a 119-item self-report questionnaire to provide clinical symptom data and other information such as illness course and functional impairment. Subclasses were generated using a principal components-like analysis followed by latent profile analysis (LPA). RESULTS: 744 subjects returned complete data sets (mean age 40.8 years, mean length of illness 7.9 years, female to male ratio 3:1). Overall, the subjects had a high rate of reporting typical CF symptoms (fatigue, neuropsychological dysfunction, sleep disturbance). Using LPA, two subclasses were generated. Class one (68% sample) was characterized by: younger age, lower female to male ratio; shorter episode duration; less premorbid, current and familial psychiatric morbidity; and, less functional disability. Class two subjects (32%) had features more consistent with a somatoform illness. There was substantial variation in subclass prevalences between the study centres (Class two range 6-48%). CONCLUSIONS: Criteria-based approaches to the diagnosis of CF and related syndromes do not select a homogeneous patient group. While substratification of patients is essential for further aetiological and treatment research, the basis for allocating such subcategories remains controversial.